A Methodology for Estimating Radiofrequency Signal Attenuation from Rainfall and Atmospheric Gases in 5g-And-Beyond Networks - Adasme-Soto, P; Ayub-, M (John Wiley and Sons Inc, 2025)
Industrial applications demand ultra-reliable and low latency communications, especially in Industrial Internet of Things (IIoT) environments. To meet these expectations, telecommunication network technologies have evolved, culminating in the deployment of fifth-generation (5G) networks by telecom operators worldwide. However, 5G and beyond networks, operating in millimetre-wave frequency bands, can suffer signal degradation caused by atmospheric phenomena, such as rainfall and atmospheric gases. This article presents a significant contribution to scientific research by proposing a methodology that leverages ITU-R recommendations (P.530, P.837, P.838, P.618-13, P.839-4, P.1511-2) for rain-induced attenuation and incorporates local meteorological data using the Gumbel Distribution. Also, the methodology considers ITU-R Recommendations (P.676, P.836, P.835) for atmospheric gas-induced attenuation. A comprehensive flowchart demonstrates the practical application of these recommendations, enabling accurate assessment of signal attenuation for various cities around the world with distinct geographical coordinates. The dataset is obtained from local Meteorological Stations or using digital maps from ITU recommendations. The results obtained with the approximate values of precipitation rates using the proposed method were compared with values from the ITU s study group and verified the effectiveness of the proposed approach, with relative errors not exceeding 1.07%. These analyses indicated the potential impact of atmospheric conditions on 5G network performance, offering valuable insights for optimising network design and improving communication reliability that is relevant to IIoT applications. © 2025 The Author(s). IET Networks published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology.